2006
DOI: 10.1038/sj.onc.1209625
|View full text |Cite
|
Sign up to set email alerts
|

MYC activation associated with the integration of HPV DNA at the MYC locus in genital tumors

Abstract: To determine whether integration of human papillomavirus (HPV) DNA sequences could lead to the deregulation of genes implied in oncogenesis, we analysed the HPV integration sites in a series of nine cell lines derived from invasive genital carcinomas. Using in situ hybridization, HPV16 or 18 sequences were found at chromosome band 8q24, the localization of MYC, in IC1, IC2, IC3, IC6 and CAC-1 cells and at other sites in IC4, IC5, IC7 and IC8 cells. We then localized viral sequences at the molecular level and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
113
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 59 publications
(86 reference statements)
9
113
0
6
Order By: Relevance
“…For instance, it has been shown that MYC activation secondary to the insertion of HPV16 or 18 genome at the MYC locus was preferentially associated with adenocarcinoma. 42 It is thus possible that secondary genetic alterations play a role in the differentiation of tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that MYC activation secondary to the insertion of HPV16 or 18 genome at the MYC locus was preferentially associated with adenocarcinoma. 42 It is thus possible that secondary genetic alterations play a role in the differentiation of tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Histological and virological analyses have shown that 3 groups of genital HPV could be identified according to their oncogenic properties. Low-risk HPVs (HPV6, 11,42,43,44. .…”
mentioning
confidence: 99%
“…The 8q24 region has also been shown to be a frequent site of HPV integration and is often amplified in cervical cell lines and cervical lesions. [25][26][27][28][29] MYC genes are key regulators of cell proliferation, and enhanced expression of MYC genes promotes unrestricted proliferation and contributes to the genesis of most human tumors. 30 The 3q26 chromosome region was proposed as an important marker for disease progression in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…The physical state of the virus and its interaction with the host genome in HPV-associated tumors has been well-characterized in cervical cancer (24)(25)(26)(27)(28)(29)(30), but less is known about the molecular architecture of HPV infection in HNC (31,32). Recently, a comprehensive genome-wide analysis of HPV integration in human cancers showed associations between HPV integrants and extensive host genomic amplifications and rearrangements, including deletions, inversions, and chromosomal translocations (12).…”
mentioning
confidence: 99%